¿Platón enemigo del arte? (Minerva, 2019)
The things in the world, not least the products of the Fine Arts as well as of poetry, are not representations of the beautiful, and Plato does not admit to «his» polis either artists or their art as they are, inasmuch as those products are not likenesses of the idea of the beautiful, of the beautiful man, the beautiful thing. Notwithstanding, Plato was not only an artist himself but a connoisseur of the Fine Arts, to the highest degree, and objectively the elite condition of working in the Academy provided him with a position to be even an amateur of these Fine Arts.